2016
DOI: 10.1177/2168479016656030
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Access of Investigational Drugs: The Experience of the Center of Drug Evaluation and Research Over a 10-Year Period

Abstract: Background The purpose of this study was to describe the experience of the Center of Drug Evaluation and Research (CDER) with expanded access of investigational drugs. Methods Multiple searches of CDER’s document tracking system were performed to identify the number, type, and indication for all expanded access requests over the 10-year time period of January 2005 through December 2014. An additional search was performed to identify all active commercial investigational drug development programs during that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 8 publications
0
61
0
Order By: Relevance
“…The vast majority of these requests are for new single-patient INDs for emergency or nonemergency access to treatment. 1 FDA recognizes that expanded access to investigational drugs can play an important role in the treatment of patients with serious or life-threatening diseases or conditions. While FDA supports patient access to investigational drugs, enrollment in clinical trials is the preferred option for eligible patients wishing to gain access to investigational drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of these requests are for new single-patient INDs for emergency or nonemergency access to treatment. 1 FDA recognizes that expanded access to investigational drugs can play an important role in the treatment of patients with serious or life-threatening diseases or conditions. While FDA supports patient access to investigational drugs, enrollment in clinical trials is the preferred option for eligible patients wishing to gain access to investigational drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous reviews of the Center for Drug Evaluation and Research (CDER) experience with expanded access, we have shown that more than 1000 applications are received each year, more than 99% of the individual access requests are allowed to proceed, the median review time is 4 days for nonemergency requests and less than 24 hours for emergency, and that FDA requests changes in 11% of those allowed to proceed to ensure patient safety. 1,2 Moreover, it is extremely rare for serious adverse events or deaths that occur under expanded access to interrupt the development program for an investigational drug.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of almost 11,000 expanded access requests over a 10-year period, however, demonstrated that only two drug development programs were placed on clinical hold due to adverse events observed in patients receiving expanded access, and even these were temporary. 10 Therefore, it is very rare for an adverse event occurring during expanded access to adversely affect drug development.…”
Section: Individual Patient Access To Investigational Drugsmentioning
confidence: 99%
“…The EMA provides recommendations through the Committee for Medicinal Products for Human Use (CHMP) for “Compassionate Use” ( 2 ), which recognizes two situations of exceptional application of a non-licensed medicinal product to patients: those applicable for a cohort of patients as “Compassionate Use” and those for “Named Patient Use” ( 2 ) ( Table 1 ). The early access equivalent in the USA is known as “Expanded Access,” which can be granted for three types of investigational new drug (IND) use: (1) individual patient IND use; (2) limited use for an intermediate-size IND patient population; and (3) treatment IND for widespread use ( 4 , 7 ). Similarities and differences in regulatory and ethical challenges between EAP programs in Europe and the USA are illustrated in Table 1 .…”
mentioning
confidence: 99%